Sediment Transport Modelling With Shen and Hung Models For Analysis Prediction Of Sediment Increase in Upper Serayu Barrage - Teguh Marhendi; Ali Imron (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2022)
Serayu Barrage is one of the weirs built in the river segment with a gentle slope of the riverbed. Serayu barrage, which was built in 1993, is used to meet the needs of irrigation water for irrigation areas Gambarsari - Pesangrahan with an area of ± 20,795 ha of irrigated land and to meet the needs of raw water in Cilacap Regency. Because this weir is located in a sloping river segment, with these characteristics the weir will easily increase sediment upstream of the weir due to the low flow velocity of the upstream weir. This study is intended to analyze the increase in sedimentation in the upstream weir based on Shen and Hung's model of sediment transport analysis. An analysis of the increase in sediment upstream of the weir was carried out for the study year from 2007-2036. The results of this study indicate that the increase in sedimentation upstream of the Barrage of Serayu's motion continued throughout the years 2007-2036. Then with using predictive analysis of the second order polynomial model, until 2036, occurs increased sedimentation in the upstream Serayu Barrage of 15,392 tons/day.Keywords: Shen and Hung sediment transport model, Increased sedimentation, Upper Serayu barrage